Evaluating bone marrow oedema patterns in musculoskeletal injury. Issue 13 (11th April 2012) - Kozoriz, Michael Gregory; Grebenyuk, Julia; Andrews, Gordon; Forster, Bruce B
Abstract : MRI is a common tool in the evaluation of musculoskeletal injury that allows the clinician to pinpoint specific pathologies. The patient's history and physical exam play a critical role in the diagnosis of sports injuries, however, complementary imaging can play an important role in determining the nature and extent of injury. With the widespread use of MRI, attention has focused on the signals generated following injury. In particular, bone marrow oedema (BME) patterns can be used to aid in the diagnosis of musculoskeletal injury. In this pictorial essay, the authors will demonstrate common patterns of BME that accompany a wide range of musculoskeletal injuries. It is expected that by the end of this article, the reader will be able to (1) recognise BME is a phenomenon observed on MRI following sports injury; (2) recognise typical patterns of BME; (3) understand the relationship of oedema to the type of injury and (4) in the presence of oedema, understand other co-existing injuries that ultimately may have an impact on management.